"PROSPECTS AND OPPORTUNITIES OF INCLUSIVE EDUCATION IN THE HIGHER EDUCATION SYSTEM, CHALLENGES AND SOLUTIONS." - Normanova Gulnora Mamadaliyevna, (Ustozlar uchun, 2025)
This article explores the prospects and opportunities of inclusive education within the higher education system, emphasizing the importance of creating accessible learning environments for all students, regardless of their physical, mental, or socio-economic backgrounds. It examines the current state of inclusive education in universities and other higher education institutions, highlighting the various initiatives aimed at fostering diversity and equity. The article also identifies key challenges faced by educators and institutions in implementing inclusive practices, such as limited resources, institutional resistance, and inadequate teacher training. Finally, the paper offers potential solutions, including policy reforms, enhanced support services, and collaborative approaches to ensure that higher education becomes more inclusive, equitable, and supportive for all students.